(untitled) (IIUC Business Review, 2021)
Islamic Banks are playing an important role in the economic expansion of Bangladesh. There are ten Islamic Banks working in Bangladesh economy. The present study is to explore the factors of dividend policy of Islamic Banks in Bangladesh. The research is based on only secondary data and sample of seven Islamic banks out of ten Islamic banks. The relevant data have been gathered from annual report of sample companies from 2010-2020. Descriptive statistics and multiple regressions are used to examine the data. This study revealed that firm size as well as liquidity have substantial positive influence and financial leverage has significant adverse effect. The study appears to convey an immense academic value since a limited research have been commenced in this ground. It may be supportive to the possessors of Islamic Banks, Management, Educational researcher and the policy makers who have been creating endeavor to the progress of Islamic Banks as well as the economy of the country as a whole. IIUC Business Review Vol. 10, Dec. 2021 pp. 69-80